Strategies and tools to learn from work that goes well within healthcare patient safety practices: a mixed methods systematic review - Gørill Birkeli; Anne Karin Lindahl; Åse Marit Hammersbøen; Ellen Catharina Tveter Deilkås; Randi Ballangrud (BMC Health Services Research)
Abstract Background Safety-II is a new approach to patient safety that is characterised by learning from work that goes well, including learning from success and work-as-done. Practical tools to facilitate this learning are starting to emerge within healthcare patient safety practices. In absence of a systematic review of such learning tools, the aim of the study was to provide an overview of strategies and tools for healthcare professionals to learn from work that goes well in healthcare patient safety practices. Methods Registered in advance in PROSPERO, this systematic review has followed the PRISMA 2020 checklist. We searched eight databases in February 2023: Medline, Cinahl, Embase, PsycInfo, Cochrane Central, Web of Science, Scopus, and Google Scholar. Articles describing the development, implementation or evaluation of tools were included if they were (1) quantitative, qualitative, mixed-methods or white papers/commentaries (non-empirical), (2) available in English or Scandinavian language, (3) published between 2000 and February 2023, (4) developed or implemented in healthcare practices, (5) detailed in description and (6) preferably peer-reviewed. Articles were excluded if they primarily dealt with students, Functional Resonance Analysis Method (FRAM), appreciative inquiry and positive deviance. Articles were screened against eligibility criteria using Rayyan software. The Mixed Methods Appraisal Tool was used to assess the quality of the articles. The framework for resilience research was used to present and synthesise the results. Results Out of 5298 records screened, 126 articles were retrieved for evaluation, and 22 articles were included, describing 16 unique tools. Five tools were not empirically evaluated. Most learning tools were aimed at healthcare professionals in hospitals units (68%), and were generally welcomed by healthcare professionals. Tools intended for learning across the organisation were second most frequent (23%), followed by tools intended for learning between hospitals (9%). Most studies focused on validating the tools’ ability to provide insights into work-as-done, and their effect on staff wellbeing. Few studies focused on patient outcomes. Conclusions The review shows a growing number of practical Safety-II tools, which may help understand and learn from the constant adaptations made by healthcare professionals every day to keep patients safe. Trial registration PROSPERO: number CRD42022335758.